1999
DOI: 10.3758/bf03211554
|View full text |Cite
|
Sign up to set email alerts
|

Recency and lexical preferences in Spanish

Abstract: One experiment provided evidence in support of Gibson, Pearlmutter, Canseco-Gonzalez, and Hickok's (1996) claim that a recency preference applies to Spanish relative clause attachments, contrary to the claim made by Cuetos and Mitchell (1988). Spanish speakers read stimuli involving either two or three potential attachment sites in which the same lexical content of the two-site conditions appeared in a different structural configuration in the three-site conditions. High attachment was easier than low attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
(41 reference statements)
0
27
0
2
Order By: Relevance
“…Results from Gibson, Pearlmutter, and Torrens' (1999) study of three-site ambiguities in Spanish provide further support for the Recency-Predicate-Proximity interaction. Gibson et al (1996) argued that the relative strength of the Predicate Proximity principle is variable, which makes it possible for it to outrank Recency in some languages or in situations where computational resources are short.…”
Section: (7) Recencymentioning
confidence: 65%
See 1 more Smart Citation
“…Results from Gibson, Pearlmutter, and Torrens' (1999) study of three-site ambiguities in Spanish provide further support for the Recency-Predicate-Proximity interaction. Gibson et al (1996) argued that the relative strength of the Predicate Proximity principle is variable, which makes it possible for it to outrank Recency in some languages or in situations where computational resources are short.…”
Section: (7) Recencymentioning
confidence: 65%
“…In addition, there is evidence from both offline and online studies that semantic properties of the linking preposition affect adult speakers' attachment decisions in two-site contexts. The findings from Gibson et al's (1996) and Gibson, Pearlmutter, and Torrens' (1999) studies indicate, however, that these "preposition effects," or lexical biases, can be overridden if the complexity of the overall NP is increased.…”
Section: (7) Recencymentioning
confidence: 98%
“…Although no single theory yet explains why we see precisely the memory-based and expectation-based patterns in the circumstances we do, expanding the scope of inquiry across languages raises prospects for clarifying this picture and thereby advancing our fundamental understanding of online language comprehension. In cases of ambiguity resolution, our understanding has already benefited considerably from a broader cross-linguistic view (Brysbaert & Mitchell, 1996; Cuetos & Mitchell, 1988; Cuetos, Mitchell, & Corley, 1996; Desmet, Brysbaert, & de Baecke, 2002; Gibson, Schütze, & Salomon, 1996; Gibson, Pearlmutter, & Torrens, 1999; Mitchell & Brysbaert, 1998). With the present studies we hope to contribute to similar advances in our understanding of syntactic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated a much studied syntactic ambiguity, namely the attachment of a relative clause to two possible noun phrases (e.g., Brysbaert & Mitchell, 1996;Cuetos & Mitchell, 1988;Desmet et al, in press;De Vincenzi & Job, 1995;Fodor, 1998;Gilboy et al, 1995;Hemforth et al, 2000;Mitchell, Cuetos, Corley, & Brysbaert, 1995;Scheepers, 2003;Traxler, Pickering, & Clifton, 1998; and see Desmet & Gibson, 2003;Gibson, Pearlmutter, Canseco-Gonzalez, & Hickok, 1996;Gibson, Pearlmutter, & Torrens, 1999;Gibson & Schü tze, 1999;Igoa, Carreiras, & Meseguer, 1998, for similar attachment ambiguities). In Experiment 1, it was shown that native Dutch speakers were more likely to produce a relative clause that attached to the higher noun phrase in the syntactic tree configuration when they had been induced to produce a high-attachment relative clause in the previous item compared to when they had been induced to produce a low-attachment relative clause in the previous item.…”
Section: Discussionmentioning
confidence: 99%